The Effectiveness of KHI in the Effort to Minimize Case of Divorce; Case Study at the Sigli Shar'i Court - Fuad, Zainul; Harahap, Mhd Yadi; Junisa, Elvi (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2022)
This study aims to determine the effectiveness of applying the Islamic Law Compilation (KHI) to minimize divorce cases at the Sigli Sharia Court. In addition, this study is to find out the obstacles to applying the Islamic Law Compilation in the Sharia Court and the efforts made by the Sigli Syari'ah Court to minimize disputes/divorce cases based on the Islamic Law Compilation. The research method used is empirical legal research using a case study approach, a statute approach. This study uses 2 (two) theories, namely the theory of legal effectiveness and the theory of the legal system.